The IDI1/SREBP2 axis drives intrahepatic cholestasis and is a treatment target of San-Huang-Cai-Zhu formula identified by sequencing and experiments - Yan, Junbin; Nie, Yunmeng; Chen, Zheng; Yao, Jiaming; Zhang, Shuo; Chen, Zhiyun (Frontiers in Pharmacology, 2023)
San-Huang-Chai-Zhu formula (SHCZF), originates from Da-Huang-Xiao-Shi decoction (DHXSD) for the treatment of jaundice as recorded in the Chinese traditional Chinese medicine book Jin Gui Yao Lue. In the clinic, SHCZF has been used to treat cholestasis-related liver disease by improving intrahepatic cholestasis, but the treatment mechanism has not been elucidated. In this study, 24 Sprague-Dawley (SD) rats were randomly assigned to the normal, acute intrahepatic cholestasis (AIC), SHCZF, and ursodeoxycholic acid (UDCA) groups. In addition, 36 SD rats were divided into dynamic groups, namely, normal 24 h, AIC 24 h, normal 48 h, AIC 48 h, normal 72 h, and AIC 72 h groups. Alpha-naphthylisothiocyanate (ANIT) was used to induce an AIC rat model. Serum biochemical indices and hepatic pathology were detected. Part of the hepatic tissues was used for sequencing, and others were used for subsequent experiments. Sequencing data combined with bioinformatics analysis were used to screen target genes and identify the mechanisms of SHCZF in treating AIC rats. Quantitative real-time PCR (qRT-PCR) and Western blotting (WB) were used to detect the RNA/Protein expression levels of screened genes. Rats in the dynamic group were used to determine the sequence of cholestasis and liver injury. High-performance liquid chromatography (HPLC) was used to determine the representative bioingredients of SHCZF. Sequencing and bioinformatics analysis suggested that IDI1 and SREBP2 are hub target genes of SHCZF to ameliorate ANTI-induced intrahepatic cholestasis in rats. The treatment mechanism is associated with the regulation of lipoprotein receptor (LDLr) to reduce cholesterol intake and 3-Hydroxy-3-Methylglutaryl-CoA reductase (HMGCR), and 3-Hydroxy-3-Methylglutaryl-CoA synthase 1 (HMGCS1) to decrease cholesterol synthesis. Animal experiments showed that SHCZF significantly reduced the expression levels of the above genes and proinflammatory cytokine lipocalin 2 (LCN2), inflammatory cytokines interleukin 1 beta (IL-1β) and tumor necrosis factor alpha (TNF-α), thereby improving intrahepatic cholestasis and inflammation and liver injury.